Vertically Aligned Nanocrystalline Graphite Nanowalls for Flexible Electrodes as Electrochemical Sensors for Anthracene Detection - Marius C. Stoian; Octavian G. Simionescu; Cosmin Romanitan; Gabriel Craciun; Cristina Pachiu; Antonio Radoi (Sensors)
Plasma-enhanced chemical vapor deposition (PECVD) was used to obtain several graphite nanowall (GNW)-type films at different deposition times on silicon and copper to achieve various thicknesses of carbonic films for the development of electrochemical sensors for the detection of anthracene. The PECVD growth time varied from 15 min to 30 min to 45 min, while scanning electron microscopy (SEM) confirmed the changes in the thickness of the GNW films, revealing a continuous increase in the series. X-ray diffraction (XRD) analysis revealed that the crystallinity of the GNW film samples increased with increasing crystallite size and decreasing dislocation density as the deposition time increased. Electrochemical characterization of the GNW-based electrodes indicated that the electroactive area and heterogeneous electron transfer rate constant were greater for the GNW 45 min film in the carbonic material series. We present the transfer of GNW films on flexible polyethylene substrates for achieving flexible electrochemical sensors for further use in anthracene determination. The flexible GNW-based electrodes were investigated using differential pulse voltammetry (DPV) in the presence of anthracene. The results showed that the highest sensitivity in anthracene detection was provided by the sensor with the GNW film obtained after 45 min of PECVD growth. The optimization of the GNW film thickness for the development of flexible electrochemical sensors on polyethylene substrates represents a successful approach for enhancing the electrochemical performance of carbonic materials.